Forearm to fingertip skin temperature gradients in the thermoneutral zone were significantly related to resting metabolic rate: potential implications for nutrition research - Pathak, K.; Calton, E.; Soares, Mario; Zhao, Y.; James, A.; Keane, K.; Newsholme, P. (Nature Publishing Group, 2017)
© 2017 Macmillan Publishers Limited, part of Springer Nature.Background:Resting metabolic rate (RMR) should be measured in the thermoneutral zone (TNZ). Forearm to fingertip skin temperature gradients (FFG) could serve as an objective measure of this pre-condition.Subjects/Methods:Eighty-six adult Australians were studied at 25?°C in a temperature-controlled chamber. Measurements of overnight fasted RMR, respiratory quotient (RQ) and FFG were complemented by clinical biochemistry. McAuley’s Index of insulin sensitivity (McA_ISI) and presence of metabolic syndrome was determined. Physical activity was estimated from the short version of the International Physical Activity Questionnaire. Fat mass (FM) and fat-free mass (FFM) were obtained from dual-energy x-ray absorptiometry. Twenty-nine participants were assessed for changes in RMR (?RMR), RQ (?RQ) and FFG (?FFG) following a 6-month free-living period. Multiple linear regression analyses of RMR and RQ on FFG, and of ?RMR and ?RQ on ?FFG were conducted after controlling for 12 known determinants of energy metabolism.Results:There were wide between-subject variations in unadjusted FFG ranging from -4.25 to +7.8?°C. The final parsimonious model for cross-sectional observations of RMR included age, FM, FFM, McA_ISI and FFG (ß=63 kJ/d (95% confidence interval (CI): 14.2, 112.1, P=0.012)). However, FFG was unrelated to RQ.In the longitudinal cohort, adjusted ?RMR significantly associated only with ?FFG (ß=100?kJ/d (95% CI: 10.3, 189.1; P=0.030)), and adjusted ?RQ associated with ?FFG (-0.003 (95% CI: -0.005, 0.0002, P=0.038)), age and McA_ISI.Conclusions:Sizeable between-subject variations in FFG at 25?°C were associated with RMR and RQ. Monitoring FFG may serve as an objective assessment of the TNZ during RMR measurements.European Journal of Clinical Nutrition advance online publication, 5 April 2017; doi:10.1038/ejcn.2017.30.